"É preciso não ter medo, é preciso ter a coragem de dizer" : um estudo da Parresía no discurso de Carlos Marighella - Moreira, Rafael Andrade (2014)
In the practice of the care of the self, we are launched by Foucault during his two last years at the Collège de France, into the problematization of the courage of truth. His study presents the concept of parrhesia based on historical studies about the Greek culture, from the tragic to the cynics, including political philosophers. The concept of parrhesia refers to the practice of free spokenness, in other words, the practice of giving freedom to speak with frankness. The function of these practices instigated the central point of this research which aimed at investigating the ethical practices (the care of the self) that allow the subject Carlos Marighella to be considered a parrhêsiast. This research is justified by the following: First, the opportunity to investigate, on the basis of Discourse Analysis, the history of an important character of Brazilian military dictatorship. Additionally, considering that truth is unattainable by the subject himself in the simple act of knowledge, but it is achieved by the subject who must care about himself, we investigated the practices of the care of the self that constitute Carlos Marighella as a potential parrhêsiast. Our research question was: How could certain ethical practices (the care of the self), to which Marighella was subjected so as to constitute himself as a moral subject (art of existence) and whose actions comprised a moral code (fight for freedom), authorize him to be a parrhêsiast' The main objective of this research was to investigate the ethical practices (the care of the self) that allow Carlos Marighella to be considered a parrhêsiast. The specific objectives are: 1) to describe the conditions of production of the corpus; 2) to reflect on the practices of subjectivation (the ethics of existence) for the government of self and others; 3) to analyze the discourse of Marighella, offering clues that prove his discourse as parrhesia. The methodology of this research is based on the theoretical principles advocated by Michel Foucault. Thus, considering the "subject position" of the guerrilla and the potential regularity present in the discontinuity of our corpus, the ordering and entering into our enunciative series were performed on the basis of a regularity possibly guided by the subject's act of resistance against military dictatorship in Brazil. Our theoretical framework was based on the concepts of Discourse Analysis, particularly on the discussions by Michel Foucault, considered highly productive for this field of study. In order to achieve the objectives of this research, we selected enunciative series from the following literary works: Porque resisti à prisão: Of which first edition is from 1965. Nevertheless, we used the book third edition issued in 1995. Manual do guerrilheiro urbano: Written in 1969 and disclosed in a mimeographed version. The corpus was chosen on the basis of what Foucault explains about the material we have and lean upon. According to the philosopher, before devoting ourselves to a potential discursive homogeneity inscribed, for instance, in a single piece of work, the material subject to analysis must be considered as a "population" of events. Thus, the analyses of the enunciative series comprising our corpus led us to conclude that Marighella was a subject that used parrhesia to act against tyranny. He acted by means of the ethical practices that constituted him as the subject of a discourse of resistance and by means of exercises that allowed gaze deviation from which Marighella took care of his soul and body to effectively govern the others.